Analysis of The Influence of Brand Equity, Trust, and Facilities on Consumer Decision-Making (Case Study on Tour & Travel Services Hajj Umrah Asbihunu Ponorogo): Analysis of The Influence of Brand Equity, Trust, and Facilities on Consumer Decision-Making (Case Study on Tour & Travel Services Hajj Umrah Asbihunu Ponorogo) - Wawan Putra; Dhika Amalia Kurniawan; Hamidah Tussifah (Islamic Business and Management Journal, 2023)
This research aims to test the influence of brand equity, trust, against the decision of the consumer in using the services of ' Umrah Hajj travel tour & ASBIHU NU Ponorogo. This type of research is kuatitatif by using a questionnaire, techniques. Data obtained through surveys to the 128 respondents i.e. consumers who have been using the services of the travel and tour & measured using the Likert scale. Sampling using a probability sampling technique with simple random sampling. Analysis tool used is the Statistical product service solution (SPSS), by conducting test validity and reliability as well as classic assumption test and test multiple linear assumption. The results showed that the variable dimension of brand awareness and perceived quality do not affect positively and significantly to consumer decision-making in using the services of the travel Hajj umrah tour & ASBIHUNU Ponorogo whereas variables brand loyalty, brand association, trust, and the facility is a positive and influential variables significantly to consumer decision-making in using the services of the travel Hajj umrah tour & ASBIHUNU Ponorogo. The suggestions can be submitted with regard to the results of this research are as follows (1) services of tour travel Hajj umrah & ASBIHUNU Ponorogo should always improve or maintain an influential factors towards positive decisions the consumer in using the services of a tour travel Hajj umrah & ASBIHUNU Ponorogo, as kesetian consumer ASBIHUNU, ease of product consumers in the given Service ASBIHUNU Ponorogo, leisure facilities when used, as well as consumer confidence against the service ASBIHUNU, Ponorogo. (2) as well as evaluate and pay more attention to factors which do not affect the consumer's decision against positive pengabilan i.e. knowledge about consumer ASBIHUNU Ponorogo, description and the generalisation of quality Services ASBIHUNU Ponorogo, as well as convenience consumer terhadapa services ASBIHUNU Ponorogo.